Orientasi kewirausahaan terhadap kinerja usaha - Riska Puspitasari (Pelantar Press, 2022)
This study aims to determine the effect of entrepreneurial orientation on business performance in students. This type of research uses the method of library research (library research). The results of the research on entrepreneurial orientation which consist of aspects of innovation have a significant effect on business performance of business actors carried out by students. Entrepreneurial orientation has an effect on business performance, these results are able to increase entrepreneurial orientation and are able to improve business performance in students.